Related‐key rectangle cryptanalysis of Rijndael‐160 and Rijndael‐192. Issue 5 (1st September 2015) - Wang, Qingju; Liu, Zhiqiang; Toz, Deniz; Varici, Kerem; Gu, Dawu
Abstract : In this study, the authors present the first related‐key rectangle cryptanalysis of Rijndael‐160/160 and Rijndael‐192/192. The author's attack on Rijndael‐160/160 covers eight rounds. The attack complexities are 2 126.5 chosen plaintexts, 2 129.28 8‐round Rijndael‐160/160 encryptions and 2 132.82 bytes. Their attack on Rijndael‐192/192 covers ten rounds. It requires 2 179 chosen plaintexts, 2 181.09 10‐round Rijndael‐192/192 encryptions and 2 185.59 bytes memory. These are the currently best cryptanalytic results on Rijndael‐160/160 and Rijndael‐192/192 in terms of the number of attacked rounds. Furthermore, their results show that the slow diffusion in the key schedule of Rijndael makes it a target for this type of analysis.